Determinants of the Incidence of Hypertension in Indonesia - Nina Nurjanah; Wuri Ratna Hidayani; Isyeu Sriagustini (Journal of Public Health Sciences, 2023)
Indonesia is ranked first in non-communicable diseases (185,857 cases). The prevalence of hypertension based on the age of the elderly was 34.1% and increased by 7.6% from the previous year. This study aims to explain the factors that can be changed by the incidence of hypertension in the elderly aged 60 years in Indonesia. Research based on literature studies using Google Scholar. Accordingto the eligibility criteria, 7 articles were obtained according to the topic. The results of the study explained that the factors that can be changed are smoking habits, activity,stress, salt consumption, coffee consumption and diet. These factors have a relationship with the incidence of hypertension.